(untitled) (Revista do Centro de Estudos Portugueses, 2001)
Estudo que procura analisar a ficção de Miguel Torga através dos conceitos de Alain Badiou, mostrando-o como defensor de uma "ética das verdades" mais do que de uma "ética dos princípios", ressaltando a autonomia de suas idéias e a diferença de sua posição no contexto humanista do Neo-realismo português. This essay tries to analyse the fiction of Miguel Torga through Alain Badiou’s concepts, showing him as a defensor of an "ethics of the truths" more than of an "ethics of the principies", evidencing the authonomy of his ideas and the difference of his position in the humanist context of Neo-realism in Portugal.